Mindfulness and Student Engagement: The Mediation Effect of Self Esteem - Artika, Munik Yuni; Sunawan, Sunawan; Awalya, Awalya (Universitas Negeri Semarang, 2021)
Student engagement in learning is essential in creating active, creative, and fun learning. Unfortunately, not all students are engaged cognitively, emotionally, and behaviorally in learning. This study intends to prove that self-esteem can mediate the relationship between mindfulness and student engagement. This correlational study involved 469 students from four Senior/Vocational High schools in East Lampung Regency. The result of this study revealed that mindfulness predicts higher self-esteem. Mindfulness predicts student engagement. Self-esteem predicts student engagement. Mindfulness also increases student engagement through increased self-esteem. The implications of this study suggest the importance of appreciating student’s mental state and performance in the learning process.